Cephalic Vein Cut Down for Total Implantable Venous Access Ports: A Retrospective Review of a Single Institution Series - Ángel Barba Vélez (EJVES Vascular Forum, 2023)
Objective: The aim of this work was to describe the early and late success rates of cephalic vein cut down (CVC) in the implantation of totally implantable venous access ports (TIVAP) for chemotherapy treatment in oncological patients. Methods: This was a retrospective study of 1 047 TIVAP performed in a private institution between 2008 and 2021. The CVC with pre-operative ultrasound (PUS) was the initial approach. All cephalic veins (CVs) were mapped pre-operatively with Doppler ultrasound, measuring their diameter and course in oncological patients who required a TIVAP. With a CV diameter ≥ 3.2 mm TIVAP was carried out by CVC; with CV diameter < 3.2 mm, subclavian vein puncture (SVP) was performed. Results: 1 047 TIVAPs were implanted in 998 patients. The mean age was 61.5 ± 11.5 years, 624 were women (65.5%). Male patients were significantly older and with a higher incidence of colonic, digestive system, and laryngeal cancer. Initially, TIVAP was indicated in 858 cases (82%) by CVC and 189 (18%) by SVP. The success rate was 98.5% for CVC and 98.4% for SVP. There were no complications for CVC (0%) but five early complications (2.5%) in the SVP group. The rates of late complications were 4.4% in the CVC group and 5.0% in the SVP group, foreign body infection being the most frequent (57.5% of the cases) (p = .85). Conclusion: The CVC or SVP using PUS for TIVAP deployment, performed through a single incision, is a safe and effective technique. This open but minimally invasive technique should be considered in oncological patients.